Pericardial Mesothelioma in a Dog: The Feasibility of Ultrasonography in Monitoring Tumor Progression - Nabeta, Rina; Nakagawa, Yuki; Chiba, Shiori; Xiantao, Hou; Usui, Tatsuya; Suzuki, Kazuhiko; Furuya, Tetsuya; Fukushima, Ryuji; Uchide, Tsuyoshi (Frontiers in Veterinary Science, 2019)
A 6-year-old neutered male Yorkshire Terrier presented with recurrent pericardial effusion. Although clinical examinations including computed tomography were inconclusive, an exploratory thoracotomy revealed multiple small nodules and plaques on the inner surface of the pericardial sac (Day 1). A subtotal pericardiectomy was performed to prevent cardiac tamponade due to the increasing pericardial effusion, and the resected section of the pericardium was histopathologically diagnosed with mesothelioma. After surgery, chemotherapy with intrathoracic carboplatin was commenced. During the course of the treatment, a detailed follow-up ultrasonographic scan was performed to detect early lesions disseminated on the pleura, originating from the primary pericardial mesothelioma. On Day 101, the minute pleural nodules, which were disseminated lesions as predicted, were successfully imaged by ultrasonography. As the clinical stage advanced, the nodules were observed to gradually increase in size and number, implying tumor progression. These observations highlight the feasibility of ultrasonography in detecting minute disseminated lesions at an early stage, monitoring tumor progression, and thereby, predicting the prognosis of canine pericardial mesothelioma.